ASSESSMENT OF MUNICIPAL UNITS IN REPUBLIC OF SAKHA (YAKUTIA) - V. L. Pulyaevskaya; В. Л. Пуляевская (Novosibirsk State University of Economics and Management, 2015)
The article provides a concept of gross municipal product. A proposed grouping on the basis of gross municipal product per capita. Presents distribution of municipal units in 2008–2012 on groups. В статье содержится понятие валового муниципального продукта. Предложена группировка на основе показателя среднедушевого муниципального продукта. Представлено распределение муниципальных образований по группам за 2008–2012 гг.